PENGARUH PENAMBAHAN CYROMAZINE PADA PAKAN TERHADAP PERTUMBUHAN POPULASI LARVA Musca domestica PADA KOTORAN UNGGAS - Septi Wulandari; Retno Hestiningsih; Mochamad Hadi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Flies are vector of disease living near human settlements and farm. In poultry, cyromazine larvicides used to control the growth of the flies by mixing into poultry feed. This application method leaving residues risk in eggs and poultry meat. Therefore, the effectiveness of flies growth inhibition due cyromazine need to be investigated. The purpose of this study was to analyze the effect of adding cyromazine in feed on the population growth of Musca domestica larvae in poultry manure. This research is a quasi experimental with posttest group only. The population is all rearing result of the first generation Musca domestica larvae, with a sample of 720 larvae. Cyromazine dose used is 1%, Poultry manure used is chicken manure and quail.The analytical method used is the analysis Growth Index (GI), Relative Growth Index (RGI), Kruskal Wallis test, and Mann Whitney test. Results showed that the GI value on chicken manure, quail manure, husk, mixture of husk and concentrate is 0,48; 0,61; 0; 1 and value RGI 48%, 61%, 0%, 100%. Statistically, they are differences  of mortality in chicken manure and quail manure (p value = 0.000 <0.05).The use cyromazine 1% in the feed is not effective to inhibit the growth of Musca domestica larvae.